Under Victimization by an Outgroup: Belief in a Just World, National Identification, and Ingroup Blame - Correia, Isabel; Pereira, Cicero R.; Vala, Jorge (Frontiers in Psychology, 2018)
Using representative probabilistic samples of Portuguese citizens and framed by an intergroup perspective, we carried out two studies aiming to address how national identification and belief in a just world (BJW) jointly predict secondary victimization of an ingroup as a whole (specifically ingroup blame). We conducted Study 1 (N= 779) in 2014, at the height of the European austerity policies imposed on Portugal by an institutional outgroup, specifically the Troika (the European Union, the European Central Bank and the International Monetary Fund). Study 2 (N= 1140) was conducted after the Troika intervention. An environment of ongoing ingroup suffering caused by an outgroup is more threatening for the BJW of individuals that are more identified with the ingroup. We therefore predicted and found that BJW was positively associated with ingroup blame in participants higher in national identification when the victimization provoked by an institutional outgroup was higher (Study 1). However, when the suffering caused by the outgroup decreased, the association between BJW and secondary victimization was not moderated by individuals’ national identification (Study 2). Indeed, a three-way interaction was found between BJW, national identification and social context (high vs. low victimization). These results are an important contribution for the literature about justice motivation in terms of intergroup relations, because they show that secondary victimization produced by a threat to BJW has a group-based identity function.